Joseph Grunwald, Miguel S. Wionczeck y Martín Carnoy. Latin American economic integration and U. S. policy. Washington, D. C. : The Brookings Institution, 1972. 216 p. - Peña, Raúl de la (Estudios Demográficos y Urbanos, 1973)
JOSEPH GRUNWALD, MIGUEL S. WIONCZECK y MARTIN CARNOY, Latin American Economic Integration and U. S. Policy, Washington, D. C., The Brookings Institution, 1972.